Numerical study of defect localization in additive manufactured short fiber reinforced composites with diffuse ultrasonic wave inspection - Peng, Yue; Xu, Hongxuan; Sun, Jingguo; Zuo, Jiancun; Zhu, Qi (Frontiers in Physics, 2022)
The structures of short fiber reinforced composites become designable from macroscopic to microscopic thanks to the advancement of additive manufacturing technologies. The diffuse ultrasonic wave inspection takes advantage of the information from multiple scattering processes, which is suitable for the quality assurance of complex structures. In this paper, a two-dimensional wave propagation model has been established assuming the fiber volume can be decoupled into the fiber distribution matrix in the plane and the local fiber fraction along thickness axis. The k-space pseudospectral method is applied to calculate the diffuse wave fields. Based on Locadiff technique, the defect inspection process is studied numerically for additive manufactured short fiber reinforced composites. The stretching method gives the same average distance but a smaller relative deviation to the defect compared to those from the doublet method. The localization resolution can be improved greatly when the number of transmitters increases initially and limited improvement can be achieved further. Localization results fluctuate when the transmitter combination groups are distant from the defect. This method works well with the isotropic and quasi-isotropic plates while an oversimplification is found for the unidirectional fiber structure.